Reconstructing runoff components and glacier mass balance with climate change: Niyang river basin, southeastern Tibetan plateau - He, Qiule; Kuang, Xingxing; Ma, Enze; Chen, Jianxin; Feng, Yuqing; Zheng, Chunmiao (Frontiers in Earth Science, 2023)
The southeastern Tibetan Plateau (TP), one of the regions with the largest glacier distribution on the plateau, has experiencing significant loss in glacier mass balance (GMB) in recent decades due to climate warming. In this study, we used the Spatial Processes in Hydrology (SPHY) model and satellite data from LANDSAT to reconstruct the runoff components and GMB in the Niyang River basin (NRB), a typical glacierized region in the southeastern TP from 1969-2013. Results show that rainfall runoff is the dominant contributor to total runoff (67%), followed by snowmelt runoff (14%), glacier melt runoff (10%), and baseflow (9%). The glacier area decreased by approximately 30% at a rate of 10.5 km2/a during 1987-2013. The NRB experienced a severe loss in GMB, with a mean value of -1.26 m w.e./a (corresponding to a cumulative glacier mass loss of -56.72 m w.e.) during 1969-2013. During periods Ⅰ (1969-1983), Ⅱ (1984-1998), and Ⅲ (1999-2013) glacier mass loss is simulated at rates of -1.27 m w.e./a, -1.18 m w.e./a, and -1.33 m w.e./a, respectively. Annual loss of glacier mass in the northern region of the NRB (-1.43 m w.e./a) is significantly greater than that of the southern region (-0.53 m w.e./a) from 1963-2013, largely due to temperature variations, especially in summer months. These findings enhance our understanding of how different hydrological processes respond to climate change and provide a potential method to study runoff components and GMB in other glacierized catchments worldwide.